2010
DOI: 10.3892/ol_00000067
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-sestamibi scintigraphy used to evaluate tumor response to neoadjuvant chemotherapy in locally advanced breast cancer: A quantitative analysis

Abstract: Abstract. to evaluate the tumor response to neoadjuvant chemotherapy, 99m tc-sestamibi breast scintigraphy was proposed as a quantitative method. Fifty-five patients with ductal carcinoma were studied. they underwent breast scintigraphy before and after neoadjuvant chemotherapy, along with clinical assessment and surgical specimen analysis. the regions of interest on the lesion and contralateral breast were identified, and the pixel counts were used to evaluate lesion uptake in relation to background radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Koga et al [65], Wilczek et al [70] showed a significant reduction rate of tumor: back-ground after completion of neoadjuvant chemotherapy, confirmed by tumor regression in histological study of the surgical specimen.…”
Section: Mechanisms Of Accumulation and Efflux Of 99mmentioning
confidence: 99%
See 4 more Smart Citations
“…Koga et al [65], Wilczek et al [70] showed a significant reduction rate of tumor: back-ground after completion of neoadjuvant chemotherapy, confirmed by tumor regression in histological study of the surgical specimen.…”
Section: Mechanisms Of Accumulation and Efflux Of 99mmentioning
confidence: 99%
“…A better response to chemotherapy regimen was observed in more aggressive tumors that represent a higher uptake rate reduction. The tumor necrosis resulting from chemotherapy could explain the substantial reduction in tumor size [65]. The invasive ductal carcinoma presents a higher uptake rate reduction compared to those associated to the in situ component.…”
Section: Mechanisms Of Accumulation and Efflux Of 99mmentioning
confidence: 99%
See 3 more Smart Citations